Produksi Program Acara “Pro 2 Activity” di Pro 2 RRI Semarang (Pengarah Kreatif) - Antika Yolanza; Lintang Ratri Rahmiaji (Interaksi Online, 2020)
Radio Republik Indonesia is the oldest radio station in Indonesia and is the only radio owned by the Indonesian government. As a public broadcasting institution, RRI has a vision of realizing an Indonesian public broadcasting institution as a trusted and worldwide radio. RRI has a very wide network, from Aceh to Papua. However, there are still many young people who don’t know Radio Republik Indonesia. The number of private radios that have sprung up today causes the popularity of RRI decreased. In addition, the image of RRI as news radio and radio for parents in the society, so it is considered less attractive for young people who need entertainment and the latest things. In order to make RRI and its programs known to the public, especially young people, one solution that can be done is to re-concept or re-create the program "Pro 2 Activity" with a new concept by involving students and communities as resource persons in this program. By targeting the youth as target audience, it is hoped that this program will be able to increase radio listeners, especially in Pro 2 RRI Semarang. During the program’s excecution, the author served as a creative director, who is responsible for recreate "Pro 2 Activity" program by creating creative ideas. In "Pro 2 Activity" program, the creative director is responsible for making program scripts and package scripts such as earcatchers, radio dramas (paparazy), viral interludes (selvi), and voxpop. During 8 weeks, the writer and team succeeded in producing 24 episodes of the "Pro 2 Activity" program with a duration of 3 hours in each episode and presenting the youth and communities as resource persons with the concept of the program being packaged differently from before, successfully attract listeners to listen “Pro 2 Activity Program”. Through this program, the writer and team also succeeded in increasing the number of active listeners, which initially only 3 to 4 people in each episode, with a new concept, now the active listeners of "Pro 2 Activity” program is increased 8 to 10 active listeners in each episode.